Analysis of Beginning Reading Difficulties in First Class Students at Pagundan 1st State Primary School - Nurjanah; Mia Rahmawati; Dewi Rahmawati (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research aims to describe the initial reading difficulties of class 1A students at SD Negeri 1 Pagundan, Kuningan. This research uses descriptive qualitative methods with the research subjects being teachers and class 1A students. Data was collected through interviews, observation and documentation. The research results showed that around 44.4% of students experienced difficulty in beginning reading. These difficulties include an inability to read syllables, word for word, diphthongs, clusters, and diagraphs; not yet able to read consonants; not being able to read vowels correctly and repeating and paraphrasing incorrectly; and don't know the meaning of the words. To overcome this difficulty, teachers provide special guidance to students who need greater attention. Teachers also use letter cards and story books as visual aids to make the learning process more interactive. In addition, regular reading practice is carried out both at school and at home through small groups of students to prioritize those who need additional help. Encouraging parent participation in their child's learning process is also an important part of this strategy.